Aspergillus fumigatus-specific immunoglobulin levels in BALF of CF patients. Issue 4 (17th November 2017) - Goña-Höpler, Mia; Pfaller, Birgit; Argeny, Jonathan; Kanolzer, Stefan; Gruber, Saskia; Schmidthaler, Klara; Renner, Sabine; Nachbaur, Edith; Fucik, Petra; Glaser, Andreas G.; Debiasi, Markus; Szépfalusi, Zsolt; et al.
A lack of correlation between systemic and local IgE production at mucosal sites has been reported for allergic asthma [1–5], allergic rhinitis [6, 7] and chronic rhinosinusitis with nasal polyps [8–10]. In allergic asthmatics, local IgE production is higher than in nonallergic asthmatics [3] and high local IgE levels have been linked to the clinical phenotype. Interestingly, in cases of nasal polyps, local IgE targets mainly superantigens [8]. IgE responses to Aspergillus fumigatus in cystic fibrosis lungs http://ow.ly/XXwv30furqs